Adhesion regulation and the control of cellular rearrangements: From emulsions to developing tissues - Montel, Lorraine; Guigue, Quentin; Pontani, Lea-Laetitia (Frontiers in Physics, 2022)
Cell rearrangements are critical for tissue remodeling during diverse biological processes, such as morphogenesis or cancer progression. They control tissue fluidity and can lead to irreversible shape changes in cohesive tissues. However, the completion of such rearrangements is strongly conditioned by intercellular adhesion, that can prevent their completion or conversely promote them along a given pattern. In this review we explore how intercellular adhesion impacts cell rearrangements at the local scale and how it translates into macroscopic mechanical properties in biological tissues. We first describe general principles obtained from the study of dispersed materials, such as emulsions, in which the mechanical properties and interaction potential between individual particles can be described in a quantitative manner. We then review the effect of varying cell-cell adhesion on rearrangements in in vitro model tissues, from cell aggregates to 2D epithelial-like cellular layers. We finally consider developing tissues in which adhesion between the cells is strongly tuned and localized in order to allow for function and shape emergence in the embryo.